海洋透光層中穩定鈣同位素的分化:生物或非生物作用及陸地與海洋沉積物中鈾系不平衡及其環境意義 - 游鎮烽; 羅尚德 (2012)
計畫編號:NSC101-2611-M006-002 執行機構:國立成功大學地球科學系 研究期間:2012-08~2013-07 全球碳循環是地球動力系統中傳輸各式碳種類的重要過程之一。海水中碳酸鈣的生成或溶解是控制海洋碳循環的重要機制，在這些過程中海水溶解鈣濃度和總鹼度變化將靈敏反應出碳酸鈣的生成或溶解作用，也因此海水總鹼度變化已被使用於診斷碳酸鈣循環工具；然而此應用卻面臨三重假設的挑戰：(1) 碳酸鈣的生成或溶解是唯一影響海水總鹼度的因素；(2) 海水總鹼度測量不受其它有機鹼的干擾；(3)氣膠物質對表面海洋鈣濃度效應的影響未被低估。實際去分別評估或檢驗影響海洋碳循環的物理、化學或生物過程是非常困難而繁雜工作；此計畫將與美國喬治亞大學蔡衛軍教授合作，利用取自2010及2012(預定)北極夏天融冰後一序列海水剖面來探討主要影響表面海水鈣循環的主要因素。我們將利用鈣和鍶同位素稀釋法以準確測量濃度海水鈣和鍶濃度剖面，高精確度非傳統鈣和鍶同位素比值MC-ICPMS分析將可協助鑑定海水中溶解碳酸鈣或鍶的可能來源，包括長程傳輸、周圍陸地或融冰稀釋作用。配合珊瑚培養箱實驗(與香港大學Goodkin教授合作)將評估表面海洋生物攝取鍶和鈣過程所造成元素或同位素分化效應；另一方面，不同控制環境下無機沉澱批次實驗結果，將可用於驗證表面海洋影響鍶/鈣遷移和其伴隨同位素分化效應的基礎機制。此三年計畫將提供更進一步對海洋碳循環瞭解的關鍵資料，並量化海洋上層透光帶中鍶和鈣來源及移出過程效率。 The global carbon cycle is an important process transporting various types of carbon species among major components in the Earth dynamic system. The formation and dissolution of calcium carbonate (CaCO3) in seawater is an important component controlling the oceanic carbon cycle. Within the process, the dissolved Ca and total alkalinity (TAlk) changes corresponding to the production or dissolution of carbonates. Thus the variation of TAlk in seawater has been used for dialog the carbonate cycle. However, it has faced a three-fold challenge: (1) the only factor to change TAlk is carbonate formation/dissolution; (2) TAlk measurements are subject to interferences from dissolved organic bases; and (3) under-estimated the effects of eolian sources to shallow seawater. It is rather difficult to isolate and to validate the physical, chemical, or biological processes that can alter the carbon cycle in shallow water. In this proposal (collaborated with Professor WJ Cai at UGA), a series of seawater profiles collected from Arctic Sea after ice melting in summer 2010 and 2012 (planed) will be used for investigating the main factors that affecting the Ca cycle at shallow seawater. Isotopic dilution mass spectrometry (IDMS) technique will be established to perform high precision Ca profile in seawater. In order to identify potential sources of Ca at shallow water, high precision Sr isotopic determination will be applied for separating source of carbonate dissolution either derived from long-distance transported eolian dust, local input or dilution effect due to ice-melting. The coral culture experiments (collaborated with Professor N Goodkin at HKU) will be used to assess the effects of biological uptake to fractionate the Ca or Sr isotopes in seawater. On the other hand, batch inorganic precipitation experiments performed under various environment conditions will be used to evaluate basic mechanisms that influencing the extent of Ca removal and associated isotopic fractionation at shallow seawater. This project will provide critical insights for a better understanding of carbon budgets at the ocean surface, as well as to quantify potential sources and removing processes of Ca and Sr at the oceanic photic zone.